Assessment of Individuals with Primary Progressive Aphasia - Henry, Maya L.; Grasso, Stephanie M. (Seminars in Speech and Language, 2018)
Speech–language pathologists play a crucial role in the assessment and treatment of individuals with primary progressive aphasia (PPA). The speech–language evaluation is a critical aspect of the diagnostic and rehabilitative process, informing differential diagnosis as well as intervention planning and monitoring of cognitive-linguistic status over time. The evaluation should include a thorough case history and interview and a detailed assessment of speech–language and cognitive functions, with tasks designed to detect core and associated deficits outlined in current diagnostic criteria. In this paper, we review assessments that can be utilized to examine communication and cognition in PPA, including general aphasia batteries designed for stroke and/or progressive aphasia as well as tests of specific cognitive-linguistic functions, including naming, object/person knowledge, single-word and sentence comprehension, repetition, spontaneous speech/language production, motor speech, written language, and nonlinguistic cognitive domains. The comprehensive evaluation can inform diagnostic decision making and facilitate planning of interventions that are tailored to the patient's current status and likely progression of deficits. As such, the speech–language evaluation allows the medical team to provide individuals with PPA and their families with appropriate recommendations for the present and the future.
Keywords: primary progressive aphasia; assessment; diagnosis; dementia